2019
DOI: 10.1097/corr.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

Is Parkinson’s Disease Associated with Increased Mortality, Poorer Outcomes Scores, and Revision Risk After THA? Findings from the Swedish Hip Arthroplasty Register

Abstract: Background Neurological conditions such as Parkinson's disease are commonly accepted as a risk factor for an increased likelihood of undergoing revision surgery or death after THA. However, the available evidence for an association between Parkinson's disease and serious One of the authors (MM) reports grants from Zimmer Biomet (Warsaw, IN, USA), personal fees from Zimmer Biomet, and grants from Link Sweden, outside the submitted work. Each author certifies that his or her institution approved the human protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 32 publications
(58 reference statements)
2
27
0
Order By: Relevance
“…Two of our patients suffered from transient delirium and were controlled with olanzapine, which confirmed that orthopedic surgery could induce a cognitive decline in PD patients [20]. Recently, some database studies [2126] showed both TKA and THA in PD patients provide a higher complication rate, longer LOS, and higher charges than the controlled cohort. One study [27] considered the higher complication rate of PD patients was associated with cardiovascular and psychiatric comorbidity.…”
Section: Discussionsupporting
confidence: 68%
“…Two of our patients suffered from transient delirium and were controlled with olanzapine, which confirmed that orthopedic surgery could induce a cognitive decline in PD patients [20]. Recently, some database studies [2126] showed both TKA and THA in PD patients provide a higher complication rate, longer LOS, and higher charges than the controlled cohort. One study [27] considered the higher complication rate of PD patients was associated with cardiovascular and psychiatric comorbidity.…”
Section: Discussionsupporting
confidence: 68%
“…Rondon et al 26 employed the longest follow-up; 10-year implant survivorship was significantly worse in PD patients compared to elective THA in matched controls (p = 0.0024). In concordance, Wojtowicz et al 22 showed patients with PD were at higher risk of revision one year (1.03% vs. 2.10%, p = 0.256) and nine years (5.44% vs. 1.75%, p = 0.001) after the primary procedure compared to matched controls. The five-year survival rate in the PD population was reported in two studies 23 , 24 (79.7% and 93%).…”
Section: Resultssupporting
confidence: 58%
“…Mortality and surgical site infection for all eligible studies reporting crude rate of events are presented in Tables 3 and 4 . In the most recently published study, Wojtowicz et al 22 reported no difference in mortality at 90 days and one year between PD and non-PD patients undergoing total hip arthroplasty (THA) (risk of death at 90 days, 0.62% vs. 0.61%, p = 0.998, and at one year 2.11% vs. 2.56%, p = 0. 670).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…coder has been used in ongoing, as well as in previously published research (Berg et al, 2018;Erik Bülow et al, 2020P. H. J. Cnudde et al, 2018;Hansson et al, 2020;Jawad et al, 2019;Nemes et al, 2018;Wojtowicz et al, 2019).…”
Section: The Coder Packagementioning
confidence: 99%